From The Rentier State To The Developmental State: The Challenge Of The Algerian Economy - Chikh- Amnache, Sabrina; Mekhzoumi, Lotfi (جامعة الوادي - University of Eloued, 2023)
The rentier state is characterized by intrinsic specificities that lead to its own underdevelopment. It is a set of practices that denote the fragility of its institutions as a whole, such as corruption, clientelism, administrative delays, misappropriation of public funds, etc. The challenge for the Algerian state is the transition from a rentier state to a developmental state, while defining the levers of rupture with the oil rent, and this through the diversification of the Algerian economy.
مقال
Keywords: Algeria ; Developmental State ; Economic Diversification ; Investment Climate ; Rentier State